Noninvasive, continuous, real-time glucose measurements compared to reference laboratory venous plasma glucose values. (18th October 2019) - Hadar, Eran; Chen, Rony; Toledano, Yoel; Tenenbaum-Gavish, Kinneret; Atzmon, Yuval; Hod, Moshe
Abstract: Purpose: Current modalities for glucose monitoring are invasive and inconvenient. The search for a noninvasive technique is still ongoing, without a clinically viable product. The aim of our study was to evaluate the safety and accuracy of a novel non-invasive continuous glucometer – the Wizmi™ device. Methods: Prospective, observational, controlled clinical trial. We included healthy pregnant women designated to undergo a 3-hour oral glucose tolerance test. Each participant underwent synchronous and simultaneous glucose measurement by venous sampling of plasma glucose and non-invasive glucose by Wizmi device. Primary outcome was the accuracy of the Wizmi device as assessed by comparing between paired measurements, i.e. non-invasive glucose measurements by Wizmi versus standard plasma glucose levels, which were taken at the exact same time. Results: Thirty-two women underwent oral glucose tolerance test (OGTT), contributing 224 paired glucose measurements. Of the 224 paired measurements, all were within the clinically appropriate zones of the Clarke error grid analysis zones −208 (93%) in Zone A and 16 (7%) in zone B. Mean absolute relative difference of the Wizmi non-invasive glucose versus plasma glucose laboratory reference was 7.23% or 9.66 mg/dl. Overall, for all 224 paired measurements, across all Wizmi glucose ranges, the agreement was 86.6, 92.0, 97.8 and 99.5% for deviations within ±15, 20, 30, 40% (if glucose >80 mg/dl) or mg/dl (if glucose ≤80 mg/dl). Conclusions: Wizmi device is novel non-invasive continuous glucose monitor, safe to use, with overall high accuracy compared to a gold standard reference of plasma glucose.